The Effect of Capital Expenditure and Operational Expenditure on Investment Decision - Ony Widilestariningtyas (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is determines the extent to which capital expenditure decisions are made by listed agricultural sector companies. Companies in Indonesia are related to the value of the company in the long run.The number of companies listed on the IDX during this period was 26, and the sample size used was 10. With the help of regression analysis, the findings reveal that capital expenditure and operational expenditure have significant relationship with investment decisions. it can be concluded that the sector companies listed on the Indonesia Stock Exchange for the period 3 years 2019-2021 capital expenditure variables have a significant positive effect on investment decisions, then operational variables have an insignificant negative effect on investment decisions It is recommended that the management of agricultural sector enterprises should ensure:holistic use of all techniques, exploring risks, real options analysis and growth and portfolio management techniques involving capital assets, in valuing capital investments before taking decision. it can be concluded that the sector companies listed on the Indonesia Stock Exchange for the period 3 years 2019-2021 capital expenditure variables have a significant positive effect on investment decisions, then operational variables have an insignificant negative effect on investment decisions.